PELAKSANAAN SUPERVISI PENDIDIKAN UNTUK MENINGKATKAN KINERJA GURU DI SDN KECAMATAN PULAU RIMAU - Nurhasanah, Nurhasanah; Putri, Mika Nusa (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
The main problem that was discussed in the study was how the supervision of school principals carried out on improving teacher performance at PulauRimau SDN 14 as well as how supervision was carried out by school principals on improving teacher performance at SDN 14 PulauRimau. The purpose of this study was to determine the development of supervision at Rimau 14 SDN to find out the improvement of teacher performance at SDN 14 PulauRimau. The study uses field research methods and the research instruments used are guidelines for observation, documentation and data analysis techniques. The interview data used in this study is to use qualitative methods. The study concluded: (1) The implementation of supervision of principals in SDN 14 PulauRimau has been carried out effectively (2) the performance of teachers in SDN 14 PulauRimau is well implemented, so that teachers experience improved performance each year (3) improvement in teacher performance at SDN 14 Rimau Island has an influence on the supervision of the principal so that it has a positive impact on improving teacher performance.